Study of Prevalence of Non-Alcoholic Fatty Liver Disease in Hypothyroidism and Possible Association of Hypothyroidism with NAFLD Fibrosis Score in Odisha - Siba Prasad Dalai; Sandeep Kumar Ratha; Brijeshraj Swain (Dr. Annil Mahajan, 2024)
Introduction: Hypothyroidism is being increasingly recognized as a risk factor for developing non-alcoholic fatty liver disease (NAFLD). This study was planned to study the prevalence and evaluate any possible association between hypothyroidism and severity of NAFLD. Material and Methods: This case control study was conducted in the department of Medicine, IMS and SUM Hospital, Bhubaneswar among 50 hypothyroid patients and 50 age and sex matched control group. USG abdomen, and various biochemical parameters including TSH levels were done and NAFLD fibrosis score was calculated. Results: Out of the 50 hypothyroid cases, 42 (84%) showed fatty liver changes, whereas only 6 (12%) of controls demonstrated fatty liver changes on ultrasonography. A positive correlation was found among the various grades of NAFLD and TSH, triglyceride, and cholesterol levels (p<0.05) and slight positive correlation found between serum TSH and fibrosis score of the cases (p=0.044, r=0.167). however, a higher TSH value was not associated with raised ALT levels in cases (p>0.05, r=0.064). Conclusion: The prevalence of NAFLD in hypothyroid patients excluding all other confounding risk factors in our study was 84%. A positive correlation was found between hypothyroidism and the NAFLD fibrosis score but not with ALT levels. A larger group of NAFLD subjects secondary to hypothyroidism is required to validate such association.